The impact of private equity and venture capital investments on industry performance: evidence from Latin America - Cebulla, Johannes (2019)
The growth of the private equity industry over the last decades has risen the importance of understanding how private equity investments impact the overall economy. While the existing research has mainly focused on the impact of private equity investments on firm performance, this study examines the impact of private equity investments on industry performance. Moreover, in contrast to most of the existing private equity literature, it focuses on emerging market countries in the postfinancial crisis period, using a novel dataset provided by the Association for Private Capital Investments in Latin America (LAVCA), which contains information on private equity investments in Latin American industries between 2009 and 2018. Thus, this paper helps in understanding the impact of private equity investments in different industry settings. The study finds that employment, free cash flow, and capital expenditure of public companies grow faster in industries that receive private equity investments in the previous years. Contrarily, labor productivity and industry returns show reduced growth rates following private equity investments. The paper does not find evidence for industry spillovers regarding profitability or net debt growth.